2010
DOI: 10.1074/jbc.m109.086447
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Netrin-like Domain of Procollagen C-Proteinase Enhancer-1 in the Control of Metalloproteinase Activity

Abstract: The netrin-like (NTR) domain is a feature of several extracellular proteins, most notably the N-terminal domain of tissue inhibitors of metalloproteinases (TIMPs), where it functions as a strong inhibitor of matrix metalloproteinases and some other members of the metzincin superfamily. The presence of a C-terminal NTR domain in procollagen C-proteinase enhancers (PCPEs), proteins that stimulate the activity of astacin-like tolloid proteinases, raises the possibility that this might also have inhibitory activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
51
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(54 citation statements)
references
References 63 publications
(133 reference statements)
3
51
0
Order By: Relevance
“…PCPE2, like PCPE1, consists of two cubulin (CUB) domains (CUB1 and CUB2) involved in protein-protein interaction. While several studies have been published addressing the physiological role of PCPE1 ( 13,14 ), the function of PCPE2 remains unclear. PCPE2-defi cient (PCPE2 KO) mice are viable and fertile, and they do not show gross developmental abnormalities ( 15 ).…”
Section: Identifi Cation Of Mature and Pro-apoa-i Formsmentioning
confidence: 99%
“…PCPE2, like PCPE1, consists of two cubulin (CUB) domains (CUB1 and CUB2) involved in protein-protein interaction. While several studies have been published addressing the physiological role of PCPE1 ( 13,14 ), the function of PCPE2 remains unclear. PCPE2-defi cient (PCPE2 KO) mice are viable and fertile, and they do not show gross developmental abnormalities ( 15 ).…”
Section: Identifi Cation Of Mature and Pro-apoa-i Formsmentioning
confidence: 99%
“…The CUB domains of PCPE1 bind procollagen (82) in a cooperative manner (83), and its NTR domain can bind BMP1 and mTLL1 (84,85), suggesting that PCPE1 may act as a linker that enhances procollagen-B/TP interactions. Moreover, enhancement of pCP activity by PCPE1 is potentiated by heparin or heparan sulfate, both of which bind the PCPE1 NTR domain, procollagen, and BMP1 (85,86), suggesting that heparan sulfate proteoglycans (HSPGs) may foster procollagen processing in vivo by bolstering formation of PCPE-procollagen-B/TP complexes (85,86). HSPGs may also bind PCPEs to cell surfaces (86).…”
Section: Pcp Enhancersmentioning
confidence: 99%
“…Indeed we have previously shown that kinetic data of the binding of endostatin, the C-terminal domain of collagen XVIII (30) and of HepV, a fragment of collagen V (31), to heparin/heparan sulfate were well fitted by a heterogeneous ligand model. PCPE-1 binding to heparin is mediated by the NTR domain (17,18). Therefore, we have also characterized the binding of the free NTR domain of PCPE-1 to heparin and heparan sulfate.…”
Section: Characterization Of the Binding Of Pcpe-1 To Heparin/heparanmentioning
confidence: 99%
“…The NTR fragment of PCPE-1 has been reported to act as a weak inhibitor of matrix metalloproteinases (21). However, no inhibitory activity was detected by other investigators against a range of metalloproteinases, including MMPs-1, -2, -3, and -9, BMP-1 and different ADAMTS proteinases (18,22). The PCPE-1 molecule has been shown to be a rod-like molecule, with a length of ϳ15 nm (23).…”
mentioning
confidence: 99%
See 1 more Smart Citation